Composite rods as a steel substitute in concrete reinforcement - Pereira, C. Gonilho (2007)
The current work is concerning with the development of braided reinforced composites rods for concrete reinforcement, as a steel substitute. The research study aims to understand the mechanical behaviour of composite rods reinforced by a fibrous structure – core reinforced braided fabric. Several samples of braided reinforced composite rods were produced. Polyester fibres were used to produce the braided fabric; several types of fibres, and several combinations of fibres, were used as braided fabric core reinforcement; and polyester resin was used as polymeric matrix. The mechanical properties of braided reinforced composite rods have been evaluated under tensile. The objective was to identify the type of fibre, or combination of fibres, to be used as braided fabric core reinforcement, in order to produce composite rods with mechanical properties similar to those of steel rebars.